Pengaruh Penambahan Agregat Ban Bekas dan Limbah Botol Kaca Terhadap Karakteristik dan Kuat Tekan Batako - Dedyerianto; La Ode Asmin; La Isa (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the characteristics of the bricks and the percentage of additional shredded used tires and glass powder that meet the minimum compressive strength requirements of solid bricks (SNI-3-0349-1989). This research uses a laboratory experimental method with variations in the percentage of additives from used tires and glass powder. The results showed that by using shredded used tires and glass powder, the three types of aggregates met the quality classification of bricks according to the minimum compressive strength requirements of solid bricks (SNI-3-0349-1989) with quality standard III. The use of used tires and glass powder in bricks as an added material by replacing some of the sand from the ratio can provide a quality standard III in making bricks according to SNI 03-0349-1989. Glass powder and used tires with an average compressive strength of 60.95 kg/cm2, 55.70 kg/cm2 and 45.19 kg/cm2, the three types of aggregates are included in grade III bricks with average compressive strength.